Urinary excretion of L-carnitine, acetyl-L-carnitine, propionyl-L-carnitine and their antioxidant activities after single dose administration of L-carnitine in healthy subjects - Yu Cao; Chuan-ji Hao; Chen-jing Wang; Peng-li Li; Le-xin Wang; Hua-shi Guan; Huan-ting Li (Universidade de São Paulo, 2013)
The urine excretion of L-carnitine (LC), acetyl-L-carnitine (ALC) and propionyl-Lcarnitine (PLC) and their relations with the antioxidant activities are presently unknown. Liquid L-carnitine (2.0 g) was administered orally as a single dose in 12 healthy subjects. Urine concentrations of LC, ALC and PLC were detected by HPLC. Superoxide dismutase (SOD), total antioxidative capacity (T-AOC), malondialdehyde (MDA) and nitrogen monoxidum (NO) activities were measured by spectrophotometric methods. The 0~2 h, 2~4 h, 4~8 h, 8~12 h, 12~24 h excretion of LC was 53.13±31.36 µmol, 166.93±76.87 µmol, 219.92±76.30 µmol, 100.48±23.89 µmol, 72.07±25.77 µmol, respectively. The excretion of ALC was 29.70±14.43 µmol, 80.59±32.70 µmol, 109.85±49.21 µmol, 58.65±18.55 µmol, and 80.43±35.44 µmol, respectively. The urine concentration of PLC was 6.63±4.50 µmol, 15.33±12.59 µmol, 15.46±6.26 µmol, 13.41±11.66 µmol and 9.67±7.92 µmol, respectively. The accumulated excretion rate of LC was 6.1% within 24h after its administration. There was also an increase in urine concentrations of SOD and T-AOC, and a decrease in NO and MDA. A positive correlation was found between urine concentrations of LC and SOD (r = 0.8277) or T-AOC (r = 0.9547), and a negative correlation was found between urine LC excretions and NO (r = -0.8575) or MDA (r = 0.7085). In conclusion, a single oral LC administration let to a gradual increase in urine L-carnitine excretion which was associated with an increase in urine antioxidant enzymes and the total antioxidant capacities. These data may be useful in designing therapeutic regimens of LC or its analogues in the future. A excreção urinária de L-carnitina (LC), acetil-L-carnitina (ALC) e propionil-L-carnitine (PLC) e as suas relações com as atividades antioxidantes são presentemente desconhecidos. Líquido de L-carnitina (2,0 g) foi administrada por via oral como uma dose única em 12 indivíduos saudáveis. As concentrações urinárias de LC, PLC e ALC foram detectados por HPLC. Atividades superóxido dismutase (SOD), a capacidade antioxidante total (T-AOC), malondialdeído (MDA) e óxido nítrico (NO) foram medidas por métodos espectrofotométricos. O 0~2 h, 2~4 h, 4~8 h, 8~12 h, 12~24 h excreção de LC foi 53,13±31.36 µmol, 166,93±76.87 µmol, 219,92±76.30 µmol, 100,48±23.89 µmol, 72,07±25.77 µmol, respectivamente. A excreηão de ALC foi 29,70±14.43 µmol, 80,59±32.70 µmol, 109,85±49.21 µmol, 58,65±18.55 µmol, e 80,43±35.44 µmol, respectivamente. A concentraηão de urina de PLC foi 6,63±4.50 µmol, 15,33±12.59 µmol, 15,46±6.26 µmol, 13,41±11.66 µmol e 9,67±7.92 µmol, respectivamente. A taxa de excreηão acumulada de LC foi de 6,1% 24 horas após sua administração. Houve também um aumento nas concentrações de urina de SOD e T-COA e diminuição de NO e de MDA. Correlação positiva foi encontrada entre as concentrações de urina de LC e SOD (r = 0,8277) ou T-AOC (r = 0,9547) e correlação negativa entre a excreção de LC e NO (r = -0,8575) ou MDA (r = 0,7085). Em conclusão, a administração oral única de LC leva ao aumento gradual na excreção urinária de L-carnitina, que foi associada com o aumento das enzimas antioxidantes na urina e as capacidades antioxidantes totais. Estes dados podem ser úteis no futuro para o planejamento de esquemas terapêuticos de LC ou os seus análogos, no futuro.